1997
DOI: 10.1176/ajp.154.3.402
|View full text |Cite
|
Sign up to set email alerts
|

B lymphocyte antigen D8/17: a peripheral marker for childhood-onset obsessive-compulsive disorder and Tourette's syndrome?

Abstract: 1997; 154:402-407)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(12 citation statements)
references
References 31 publications
1
10
0
1
Order By: Relevance
“…Consequently, some authors tried determining whether the monoclonal antibody D8/D17 could also be used as an OCD marker. The D8/D17 mean value was shown to be higher in OCD or Tourette’s child populations vs. control subjects [80], and, as no difference was found between Tourette syndrome and OCD patients in D8/D17 values, it was hypothesized that it could be a marker for OCD in children [80]. Although these results were replicated [74,77], there is still debate surrounding this topic [71,73,81,84] (Table 2).…”
Section: Immunological Changes In Ocdmentioning
confidence: 99%
“…Consequently, some authors tried determining whether the monoclonal antibody D8/D17 could also be used as an OCD marker. The D8/D17 mean value was shown to be higher in OCD or Tourette’s child populations vs. control subjects [80], and, as no difference was found between Tourette syndrome and OCD patients in D8/D17 values, it was hypothesized that it could be a marker for OCD in children [80]. Although these results were replicated [74,77], there is still debate surrounding this topic [71,73,81,84] (Table 2).…”
Section: Immunological Changes In Ocdmentioning
confidence: 99%
“…PANDAS tanılı 27, Sydenham koreli 9 hasta ile 24 kişilik sağlıklı kontrol grubunun dâhil edildiği bir çalışmada, D8/17 pozitiflik oranı PANDAS, Sydenham koresi ve kontrol gruplarında sırasıyla %85, %89 ve %17 olarak bulunmuştur (17) . Çocukluk çağı başlangıçlı OKB ve/veya Tourette sendromu (bir çeşit tik bozukluğu) bulunan 31 hasta ile 21 kişilik kontrol grubunun dâhil edildiği bir başka çalışmada; hastalardaki D8/17 pozitifliği oranının kontrol grubuna göre anlamlı derecede yüksek olduğu belirtilmiştir (18) . Yapılan bazı çalışmalarda ise D8/17 belirteci pozitifliği ile OKB ve tik bozukluğu arasında bir ilişki bulunmamıştır (19,20) .…”
Section: Hastalığın Immünolojik Boyutuunclassified
“…The reported prevalence of ASO antibodies ranges from 29-69% in TS to 18-52% in healthy controls (Cardona and Orefici, 2001; Kiessling et al, 1993, 1994; Müller et al, 2000; Singer et al, 1998; Murphy et al, 1997; Morshed et al, 2001; Church et al 2003; Rizzo et al, 2006). The prevalence of antibodies to DNase B ranges from 13-85% and from 8-59% for TS and controls, respectively (Kiessling et al, 1994, Müller et al, 2000; Singer et al, 1998; Murphy et al, 1997, Morshed et al, 2001). One large, long term, population-based follow up study of children after GAS infection found a strong relationship with behavior and non tic-like motor changes but no association specifically with tics (Murphy et al 2007).…”
Section: Introductionmentioning
confidence: 99%